Environmental Factors Affecting Spatial Dinoflagellate Cyst Distribution in Surface Sediments Off Aveiro-Figueira da Foz (Atlantic Iberian Margin) - García-Moreiras, Iria; Oliveira, Anabela; Santos, Ana I.; Oliveira, Paulo B.; Amorim, Ana (Frontiers in Marine Science, 2021)
Resting cysts of planktonic dinoflagellates, once produced, sink to the seabed where they can remain viable for a long time. These cysts have important ecological roles, such as acting as the inoculum for the development of planktonic populations. Moreover, dinoflagellate cyst records from depth sediment cores are broadly used as a proxy to infer past environmental conditions. In this study, the main objective was to obtain information on the relationships between the spatial distribution of modern dinoflagellate cysts and present-day hydrography in the NW Iberian shelf. Cyst assemblages were analysed in 51 surface sediment samples with varying grain sizes, collected at different water depths, following nine transects perpendicular to the coast, between Aveiro and Figueira da Foz (Atlantic Iberian margin). Multivariate statistical analyses revealed marked land-sea and latitudinal gradients in the distribution of cysts, and helped investigate how environmental factors (water depth, grain size, sea-surface temperature (SST), sea-surface salinity (SSS), bottom temperature (BTT) and surface chlorophyll-a concentration (CHL)) influence modern dinoflagellate cyst composition and abundances. Three main ecological signals were identified in the modern dinoflagellate cyst assemblages: 1) the heterotroph signal as the main upwelling signal; 2) the dominance of P. reticulatum and L. polyedra signal, indicative of warm stratified conditions, possibly reflecting transitional environments between more active inshore upwelling and warmer offshore waters; and 3) the G. catenatum signal for the presence of mid-shelf upwelling fronts. The almost absence of viable cysts of the toxic and potentially toxic species G. catenatum L. polyedra and P. reticulatum suggests that in the study area, for these species, there is no build-up of significant cyst beds and thus planktonic populations must depend on other seeding processes. These results are the first detailed modern distribution of dinoflagellate cysts in the NW Iberian Atlantic margin (off Portugal), and show a good correspondence with hydrographic features of summer upwelling season in the study area, meaning that they are reflecting water column characteristics and therefore may be used as supporting evidence for the interpretation of stratigraphic cyst records and reconstruction of past marine ecosystems in W Iberia.